Supporting US healthcare providers for successful vaccine communication - Amanda J Pierz; Lauren Rauh; Dima Masoud; Alanna Kate Cruz; P. Christopher Palmedo; Scott C Ratzan; Ruth Parker (BMC, 2023)
Abstract Background While many healthcare providers (HCPs) have navigated patients' vaccine concerns and questions prior to the rollout of the COVID-19 vaccines, sentiments surrounding the COVID-19 vaccines have presented new and distinct challenges. Objective To understand the provider experience of counseling patients about COVID-19 vaccinations, aspects of the pandemic environment that impacted vaccine trust, and communication strategies providers found supportive of patient vaccine education. Methods 7 focus groups of healthcare providers were conducted and recorded during December 2021 and January 2022, at the height of the Omicron wave in the United States. Recordings were transcribed, and iterative coding and analysis was applied. Results 44 focus group participants representing 24 US states with the majority (80%) fully vaccinated at the time of data collection. Most participants were doctors (34%) or physician's assistants and nurse practitioners (34%). The negative impact of COVID-19 misinformation on patient-provider communication at both intrapersonal and interpersonal levels as well as barriers and facilitators to patient vaccine uptake are reported. People or sources that play a role in health communication ("messengers") and persuasive messages that impact behavior or attitudes towards vaccination ("messages") are described. Providers expressed frustration in the need to continuously address vaccine misinformation in clinical appointments among patients who remained unvaccinated. Many providers found value in resources that provided up-to-date and evidence-based information as COVID-19 guidelines continued to change. Additionally, providers indicated that patient-facing materials designed to support vaccination education were not frequently available, but they were the most valuable to providers in a changing information environment. Conclusions While vaccine decision-making is complex and hinges on diverse factors such as health care access (i.e., convenience, expense) and individual knowledge, providers can play a major role in navigating these factors with their patients. But to strengthen provider vaccine communication and promote vaccine uptake, a comprehensive communication infrastructure must be sustained to support the patient-provider dyad. The findings provide recommendations to maintain an environment that facilitates effective provider-patient communication at the community, organizational and policy levels. There is a need for a unified multisectoral response to reinforce the recommendations in patient settings.